Subtle Roles of Down Syndrome Cell Adhesion Molecules in Embryonic Forebrain Development and Neuronal Migration - Mitsogiannis, Manuela D.; Pancho, Anna; Aerts, Tania; Sachse, Sonja M.; Vanlaer, Ria; Noterdaeme, Lut; Schmucker, Dietmar; Seuntjens, Eve (Frontiers in Cell and Developmental Biology, 2021)
Down Syndrome (DS) Cell Adhesion Molecules (DSCAMs) are transmembrane proteins of the immunoglobulin superfamily. Human DSCAM is located within the DS critical region of chromosome 21 (duplicated in Down Syndrome patients), and mutations or copy-number variations of this gene have also been associated to Fragile X syndrome, intellectual disability, autism, and bipolar disorder. The DSCAM paralogue DSCAM-like 1 (DSCAML1) maps to chromosome 11q23, implicated in the development of Jacobsen and Tourette syndromes. Additionally, a spontaneous mouse DSCAM deletion leads to motor coordination defects and seizures. Previous research has revealed roles for DSCAMs in several neurodevelopmental processes, including synaptogenesis, dendritic self-avoidance, cell sorting, axon growth and branching. However, their functions in embryonic mammalian forebrain development have yet to be completely elucidated. In this study, we revealed highly dynamic spatiotemporal patterns of Dscam and Dscaml1 expression in definite cortical layers of the embryonic mouse brain, as well as in structures and ganglionic eminence-derived neural populations within the embryonic subpallium. However, an in-depth histological analysis of cortical development, ventral forebrain morphogenesis, cortical interneuron migration, and cortical-subcortical connectivity formation processes in Dscam and Dscaml1 knockout mice (Dscamdel17 and Dscaml1GT) at several embryonic stages indicated that constitutive loss of Dscam and Dscaml1 does not affect these developmental events in a significant manner. Given that several Dscam- and Dscaml1-linked neurodevelopmental disorders are associated to chromosomal region duplication events, we furthermore sought to examine the neurodevelopmental effects of Dscam and Dscaml1 gain of function (GOF). In vitro, ex vivo, and in vivo GOF negatively impacted neural migration processes important to cortical development, and affected the morphology of maturing neurons. Overall, these findings contribute to existing knowledge on the molecular etiology of human neurodevelopmental disorders by elucidating how dosage variations of genes encoding adhesive cues can disrupt cell-cell or cell-environment interactions crucial for neuronal migration.